Influence of Relative Humidity and Aging on Morphology and Chemical Composition on Biomass Burning Particle - Titinan Utavong; Thunyapat Thongyen; Surat Bualert; Parkpoom Choomanee; Saranarat Kongkeaw; Tanawan Rattanapotanan; Jitlada Phupijit; Suteekan Maneejantra; Nitchakarn Changplaiy (Aerosol and Air Quality Research)
Abstract Agricultural waste burning is a major source of fine particulate matter (FPM), which remains in long-term suspension in the atmosphere during the aging processes. This research studied changes in the size, morphology, and chemical composition of FPM produced from rice straw and sugarcane leaf burning and the effects of relative humidity (RH) on the aging process. The FPM was measured using a scanning mobility particle sizer and the particle mass was collected for morphological (transmission electron microscopy) and chemical (organic and elemental carbon, and water-soluble ions) analyses during 3, 6, and 9 h of aging. The geometric mean diameter (GMDN) of FPM from biomass burning were 95 ± 4 nm (Aitken mode) and 133 ± 40 nm (accumulation mode). The FPM changed from non-uniform and aggregate shapes in fresh particles into chain aggregates in 9 h-aged particles. The dominant chemical components of FPM were OC2, OC3, NO3 –, Na+, and K+ under low RH condition (60%). Under high RH condition (90%), the FPM had a larger GMDN and a significant influence on its morphology, as observed in coated spherical or agglomerated shapes. The results showed that the aging process, RH, and aging duration were important factors affecting the size, shape, and chemical composition of aged particles.